EFEKTIVITAS PEMBELAJARAN DARING MATA PELAJARAN BIOLOGI PADA MASA PANDEMI COVID-19 DI SMK PERTANIAN PROVINSI RIAU - Nur Amalia Khazana; Fitra Suzanti; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effectiveness of online learning for biology subjects during the covid-19 pandemic. Descriptive research was conducted at the Integrated Agricultural Vocational School of Riau Province in May-June 2022. The population in this study were all students of class X agritans, the determination of the sample was carried out by purposive sampling, the sample in this study was class X agritan 1 and agritan 3 as many as 64 students. The instruments used in data collection were closed questionnaires to students and interviews to teachers. The questionnaire used is an adoption questionnaire. The results showed that the effectiveness of online learning for biology subjects on the indicators of learning tools with a percentage of 47.57% was quite effective.Key Words: Effectiveness, Online Learning, Biology Lessons